أثر التداول النقدي على مؤشر أسعار الاستهلاك في الجزائر-دراسة قياسية للفترة (2000-2021)- - خوالد, مولود; رملي, حمزة (جامعة الوادي - University of Eloued, 2022)
This study aims to measure and analyze the impact of monetary trading on Algeria's consumer price index over a period of 21 years. It has been addressed by estimating the model and detecting a common complementarity between monetary trading and the consumer price indexaccording to the boundary approach, while estimating that relation ship in the near and long term using the auto-regression approach of the slow down deviations distributed by ARDL. The study concluded that if there is a one-unit monetary shockwave, this impact on consumer priceindex position will last for a maximum period of about 11 monthsuntil it is due to its balanced and normal position. We also concluded that there is a far-reaching balance between monetary trading and the consumer price index at the level of the Algerian economy'senvironment.
Impact of monetary trading on Algeria's consumer price index - A standard study for the period 2000-2021-
مقال
Keywords: التداول النقدي ; مؤشر أسعار الاستهلاك ; الاقتصاد الجزائري; ARDL ; Monetary Trading ; Consumer Price Index ; Algerian Economy